Monitoring of lung edema by microwave reflectometry during lung ischemia-reperfusion injury in vivo - Nowak, Kai; Schäfer, Michael; Gross, Wolfgang; Metzger, Roman Patrick; Hohenberger, Peter; Post, Stefan; Gebhard, Martha-Maria (European surgical research, 2006)
It is still unclear whether lung edema can be monitored by microwave reflectometry and whether the measured changes in lung dry matter content (DMC) are accompanied by changes in PaO2 and in pro- to anti-inflammatory cytokine expression (IFN-γ and IL-10). Right rat lung hili were cross-clamped at 37°C for 0, 60, 90 or 120 min ischemia followed by 120 min reperfusion. After 90 min (DMC: 15.9 ± 1.4%; PaO2: 76.7 ± 18 mm Hg) and 120 min ischemia (DMC: 12.8 ± 0.6%; PaO2: 43 ± 7 mm Hg), a significant decrease in DMC and PaO2 throughout reperfusion compared to 0 min ischemia (DMC: 19.5 ± 1.11%; PaO2: 247 ± 33 mm Hg; p < 0.05) was observed. DMC and PaO2 decreased after 60 min ischemia but recovered during reperfusion (DMC: 18.5 ± 2.4%; PaO2: 173 ± 30 mm Hg). DMC values reflected changes on the physiological and molecular level. In conclusion, lung edema monitoring by microwave reflectometry might become a tool for the thoracic surgeon.
Gesehen am 30.05.2022